2020
DOI: 10.1002/adfm.202007760
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Dried TiO2(B)‐Containing Photocatalytic Glass‐Ceramic Nanobeads

Abstract: Glass‐ceramic nanospheres of molar composition 0.83 SiO2 · 0.17 TiO2 are produced by the sol‐gel spray‐drying method followed by controlled heat treatments up to 1200 °C. TiO2(B) and anatase nanocrystals are precipitated in the glassy matrix: the latter phase gradually predominates with increasing ceramization temperature and time, in parallel to an overall increase in crystal sizes. The nanospheres exhibit evident photocatalytic activity under UV‐A irradiation, especially at annealing stages involving a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 51 publications
5
34
1
Order By: Relevance
“…31 Suitable amounts of LiNO 3 and Al(NO 3 ) 3 ·9H 2 O (≥98.5%, Merck) were then solved 1:1 in deionized water and added to the first solution under constant stirring, further diluting it with deionized water to 5 wt% equivalent total oxide content. As similarly detailed elsewhere, 30 50 ml of the so-obtained mixture were then spray-dried in 2 h to obtain ~2 g of amorphous nanobeads. The solution was thereby nebulized by an aerosol atomizer (Atomizer, AGK 2000, Palas) operated with pressurized air (2.9 bar) into a tube furnace set at 500°C.…”
Section: Preparation Of the Glassy Nanobeadsmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Suitable amounts of LiNO 3 and Al(NO 3 ) 3 ·9H 2 O (≥98.5%, Merck) were then solved 1:1 in deionized water and added to the first solution under constant stirring, further diluting it with deionized water to 5 wt% equivalent total oxide content. As similarly detailed elsewhere, 30 50 ml of the so-obtained mixture were then spray-dried in 2 h to obtain ~2 g of amorphous nanobeads. The solution was thereby nebulized by an aerosol atomizer (Atomizer, AGK 2000, Palas) operated with pressurized air (2.9 bar) into a tube furnace set at 500°C.…”
Section: Preparation Of the Glassy Nanobeadsmentioning
confidence: 99%
“…The initial glassy nanobeads were likely to contain some residual water and organics even after a calcination at 500°C, as observed previously in spray-dried SiO 2 -TiO 2 glassceramics. 30 This volatile content may have effectively lowered glass viscosity, facilitating the initial stages of crystallization and sintering and causing the grain coarsening and agglomeration documented by TEM (Figure 1). Concurrently, we employed an excess of Li 2 O to foster the crystallization of the samples into Qss and to suppress the formation of cristobalite, as documented in the past 31 ; please note that we demonstrated that Li 2 O volatilization F I G U R E 4 Excerpts of the X-ray diffraction measurements performed at high temperature and at cryogenic conditions, manifesting the high-low inversion of quartz solid solution in samples: (A) LA00, (B) LA05, (C) LA10, (D) LA15, (E) LA19, (F) LA21, (G) LA22, (H) LA25.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, glass-ceramic material has attracted great attention as a promising material for high temperature structural matrix [8,9]. Compared with other ceramic materials, glass-ceramic material has the advantages of better thermal stability, lower coefficient of thermal expansion [10][11][12]. Barium aluminosilicate (BaAl2Si2O8, BAS) is an advanced glass-ceramic material known for the excellent high temperature stability.…”
Section: Introductionmentioning
confidence: 99%